Microsoft Silverlight 3 [ a beginner's guide - Horn, Shannon (New York : McGraw-Hill, 2010)
"Filled with hands-on examples Microsoft Silverlight 3: A Beginner's guide covers Visual Studio 2010 and the .NET Framework 4.0. Learn how to use Silverlight to stream multimedia content across the Web, develop dynamic, data-driven Silverlight applications, access data using XML and LINQ, and create XAML and WCF services. The book shows you how to test, debug, deploy, and secure your applications."--BOOK JACKET
1. The road leading to Silverlight -- 2. .NET framework 3.5 -- 3. The Silverlight framework -- 4. Animating Silverlight -- 5. Preparing media for use in Silverlight -- 6. Communicating with the outside world -- 7. Who goes there...securing Silverlight applications -- 8. Designing Silverlight user interfaces -- 9. Working with data in Silverlight -- 10. Retrieving server resources -- 11. Debugging the deploying Silverlight applications -- 12. Developing line of business (LOB) applications
Includes index
Keywords: Application software -- Development; Multimedia systems; Web site development